2021
DOI: 10.19044/esj.2021.v17n28p35
|View full text |Cite
|
Sign up to set email alerts
|

Democratic Governance and Social Service Delivery in Africa: the case of Taraba State, Nigeria

Abstract: Postcolonial leadership is implicated in the distorted development and crisis of governance in Nigeria. The political leadership emerged from authoritarian traditions of the colonial state and pursued self-interests against collective societal interests; the mode of the emergence of the leaders as well as the context in which they operate usually impact on the nature and trend of social welfare provisioning. Relying on data from secondary sources, this study examined the impact of democratic governance on soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In his work, Umar (2006) observed that it is about regime maintenance in such ways as to prevent breakdown of political institutions and processes. For Onuoha (2010), democratic consolidation entails progressive improvement in the procedural, structural and institutional capacity of an emergent democratic state to create and promote conditions that generate support for democratic permanence and sustainability. A common denominator of Umar and Onuoha's views is that democratic consolidation is about ensuring stability of democratic process both in its institutional and behavioural contexts as well as avoiding tendencies that will not only stunt the growth but also lead to decline in the quality of democracy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In his work, Umar (2006) observed that it is about regime maintenance in such ways as to prevent breakdown of political institutions and processes. For Onuoha (2010), democratic consolidation entails progressive improvement in the procedural, structural and institutional capacity of an emergent democratic state to create and promote conditions that generate support for democratic permanence and sustainability. A common denominator of Umar and Onuoha's views is that democratic consolidation is about ensuring stability of democratic process both in its institutional and behavioural contexts as well as avoiding tendencies that will not only stunt the growth but also lead to decline in the quality of democracy.…”
Section: Resultsmentioning
confidence: 99%
“…The above views are in consonance with that of Ogundiya (2010) when he observed that the idea of democratic consolidation is about addressing the challenges of regime stabilisation and providing answer to the question as to when democracies are secure from breakdown. It also needs to be stated that contemporary scholars have often rely on Colliers categorisation of approaches to democratic consolidation (Ogundiya 2010;Onuoha 2010, Okotie, 2008. Accordingly, three approaches were discerned: actor centred which focussed on willingness of actors to act within democratic rules; event centred which has to do with elections or constitutional ratification and; the institutional consisting of both internal and external factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation